STRATEGI KOMUNIKASI EFEKTIF ANTARA GURU DAN ANAK DALAM PERKEMBANGAN BAHASA ANAK USIA DINI - Rihaadatul 'Aisy; Gustiana Yuantini; Husnul Hafidhoh (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
Teacher strategies in this research are the methods or methods used by teachers in developing language skills in early childhood. The aim of this research is to determine the effective communication strategies used by teachers in developing language skills in early childhood. This research is qualitative research using a descriptive approach. The subjects in this research were three teachers in the Hafsho class at Al Ittifaqiah Indralaya Islamic Kindergarten. Data collection techniques in this research are by observation, interviews and documentation. The data analysis technique in this research uses the Miles and Huberman model analysis technique, namely data reduction, data presentation, verification and conclusions. The research results found in this study regarding teacher strategies in developing early childhood language skills include direct communication (both with the teacher and with friends in class), role playing, singing, storytelling methods, playing with chain words, picture media and using letter cards. . After implementing this strategy by the teacher, there was very good development in the children, where all children had Very Well Developed (BSB) language skills..